Pengaruh Penyaluran Kredit, Non Performing Loan , Corporate Social Responsibility, Digital Banking terhadap Customer Retention di Bank Sumut KCP Sei Sikambing , Medan - Sihombing, Ema Ranika (Fakultas Ekonomi Prodi Akuntansi, 2025)
Technological progress plays a crucial role in the expansion of digital banking within the financial sector. Digital banking enables customers to engage with banks more efficiently, especially regarding credit distribution, non-performing loans (NPL), corporate social responsibility (CSR), and other financial services, without requiring a physical visit to a bank branch. Based on this context, this study aims to analyze the impact of credit distribution, non-performing loans (NPL), corporate social responsibility (CSR), and digital banking on customer retention at Bank Sumut KCP Sei Sikambing. The research involves a total population of 50 individuals. A probability sampling method is applied in this study. Customer retention serves as the dependent variable, whereas the independent variables include credit distribution, non-performing loans (NPL), corporate social responsibility (CSR), and digital banking. This research adopts a quantitative survey approach, with data analysis conducted using SPSS version 2020. The results of the t-test reveal that credit distribution positively affects customer retention. Similarly, non-performing loans (NPL), corporate social responsibility (CSR), and digital banking also exhibit a positive influence on customer retention.